Anteroposterior variation of the cell types in the interrenal gland of the male toad Rhinella arenarum (Amphibia, Anura) - Regueira, Eleonora (2013)
The interrenal gland of anurans synthesizes the steroids aldosterone and corticosterone, but it is unknown whether these hormones are synthesized by the same cell type. In this work, we aim to elucidate whether there are different steroidogenic cell types and whether they have specific regionalization in the interrenal gland of the male toad Rhinella arenarum. We characterized all cell types using histological, immuhistochemical, and histochemical methods as well as transmission electron microscopy. Furthermore, we evaluated the organization of the cell types in the gland and anteroposterior variations in the synthesis of the steroids. We found evidence of five cell types: two morphologically different steroidogenic cells, type 1: polyhedral cells tightly attached to each other that have spherical euchromatic nuclei and type 2: retracted cells loosely attached to each other that have oval heterochromatic nuclei. Cell type 2 is mainly observed in the inner zone of the gland. In addition, we observed two types of chromaffin cells, called type 3 and 4 cells, randomly distributed throughout the interrenal gland, as well as type 5 cells, recognized as summer cells. Morphometric analyses of the cell types in the anterior and posterior zones of the interrenal showed that the ratio "area of type 2 cells/total interrenal area" is significantly lower in the posterior zone. In vitro incubations showed that the posterior portion of the gland produces significantly higher amounts of both corticosterone and aldosterone. Overall, our results suggest that the type 2 cells are less active to synthesize both aldosterone and corticosterone, compared to type 1 cells. Unlike most previous reports on the interrenal gland of anurans, in R. arenarum there is a zonation of the steroidogenic cell types, which implies that the organ is not anteroposterior or dorsoventrally homogeneous. © 2012 Wiley Periodicals, Inc.